The Impact of Community Sports Public Services on Public Satisfaction - Hang Zhang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Objective: To explore the impact of community sports public services on public satisfaction. Methods: Sports public services are public goods or mixed goods provided by public organizations to meet public sport’s needs, that is, public departments with the government as the core, provide sports services and products to residents through various ways and means by coordinating, organizing, and allocating social public sports resources, As an essential component of building a service-oriented government, sports public services are of great significance in enhancing people's physical fitness, promoting the construction of social spiritual civilization, and improving people's satisfaction with government public services.Through literature review, various factors affecting public satisfaction with urban community sports public services were explored, and community residents in a certain city were selected as the research object. Based on questionnaire research and factor analysis, empirical tests were conducted on various influencing factors using structural equation modeling. Results: Usually, x2/df<2 indicates that the model fits well, and a range of 2-5 is acceptable; The values of GFI, AGFI, NFI, IFI, RFI, and CFI above 0.9 indicate that the model fits well; The value of RMSEA<0.05 indicates a good fit, while<0.08 indicates a good fit. The x2/df value in this study is less than 2, and GFI, CFI, and NFI are greater than or equal to 0.9. Conclusion: The quality of venue facilities construction, convenient conditions for participating in activities, quality of sports service management, and quality of sports activity guidance have a significant impact on public satisfaction with community sports public services in a certain city.